Associations of Self-Reported Periodontal Disease With Metabolic Syndrome and Number of Self-Reported Chronic Conditions - Lillian Bensley, PhD; Juliet VanEenwyk, PhD; Eric M. Ossiander, PhD (Centers for Disease Control and Prevention, 2011)
IntroductionIncreasing evidence supports associations between periodontal disease and various chronic conditions. Possible explanations include chronic inflammatory processes, shared pathogens, and shared risk factors, such as smoking and psychosocial stress. The objective of this study was to assess associations of periodontal disease with metabolic syndrome and number of chronic diseases.MethodsAs part of the Washington Adult Health Survey, a household-based cross-sectional study conducted during 2006-2007 among adults aged 25 years or older in Washington State, we collected questionnaire data, blood samples, and anthropometric measures. We used these data to assess associations of periodontal disease with metabolic syndrome and the number of self-reported chronic diseases, controlling for age, sex, annual household income, smoking, and psychosocial stress. We used both complete case and multiple imputation Poisson regression analyses.ResultsIn the adjusted complete case analysis, 1.4 times as many chronic conditions were found among people with severe compared with no periodontal disease, and people with severe periodontal disease were 1.5 times more likely to have metabolic syndrome than people with no periodontal disease. Arthritis and liver disease were individually associated with severe periodontal disease. Results of the multiple imputation analyses were similar.ConclusionThese results suggest that people with severe periodontal disease are likely to have more chronic diseases and are more likely to have metabolic syndrome compared with people without periodontal disease. Research about the effectiveness of periodontal treatment to help prevent or control chronic diseases is needed.